Advances in medical education and practice: student perceptions of the flipped classroom - Sait MS; Siddiqui Z; Ashraf Y (Advances in Medical Education and Practice, 2017)
Mohammed Salik Sait,1 Zohaib Siddiqui,2 Yasir Ashraf3 1Barts and the London School of Medicine and Dentistry, 2King’s College School of Medicine, 3School of Medicine, Imperial College London, London, UK  We read with great interest the article by Ramnanan and Pound which reviews the benefits and limitation of the “flipped classroom” (FC) approach to teaching in medical schools.1 As fifth-year medical students from three separate UK medical institutions, we appreciate the emphasis placed on the development of an effective medical school curriculum that enables students to critically engage with the both scientific and clinical concepts. We hence share our views on the development of the FC approach to teaching. View the original paper by Ramnanan and Pound